Prognostic Markers Related to Triple-Negative Breast Cancer - Imtiaz Ali Langah, Syed Moin Islam Shah, Maimoona Khushk, Abdul Rehman, Muhammad Abid Owais, Masood Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The triple-negative tumor is a high-risk tumor as a targeted therapy to these proteins is not possible with this type of cancer. Objective: To investigate the prognostic factors that can help in treatment selection in the triple-negative phenotype breast tumors Study design: A cross-sectional study Place and duration: This study was conducted at People's University of Medical and Health Sciences Nawabshah from Nov 2021 to Nov 2022 Methodology: The present study examined numerous cases of invasive carcinoma of the breast. The patients visited for follow-up for a long time and they were examined by tissue microarray. The series was stained through concurrent immune-histochemical prognostic panels. This was done to specify the subgroups of different types of breast cancer and for the identification of prognostic markers as well as the aggressive behavior of the tumors. Results: In the beginning, a total of 280 cases were included in the study, out of which 45 (16.07%) patients had triple-negative breast cancer. Most of these cancers were grade 3 carcinomas. A strong association was seen with pushing margins, development of recurrence, large size, poorer Nottingham Prognostic Index, and distant metastasis. Moreover, the association was also seen with loss of expression of E-cadherin and androgen receptors, basal phenotype, p53, EGFR, and P-cadherin. The size of the tumor, androgen receptors, and lymph node staging were the most valuable prognostic markers. Androgen receptor and size had prognostic significance in the tumor subgroup with lymph node-positive tumors. On the other hand, the basal phenotype was the only prognostic marker in the subgroup with lymph node-negative tumors. Some other parameters considered in the present study are histological grade, size of the tumor, age of the patient, and vascular invasion. Conclusion: The most significant markers identified were basal phenotype and androgen receptor. Also, tumor size and the status of the lymph node are quite significant in low-risk and high-risk patients while selecting surgical or non-surgical treatment for the triple-negative tumors Keywords: Triple-negative, breast tumor, prognostic markers, androgen receptors